SAP INTELLIGENT RPA FOR DEVELOPERS automate business processes using SAP intelligent RPA and learn the migration path to SAP process automation. - Madhuvarshi, Vishwas; Ganugula, Vijaya Kumar (PACKT PUBLISHING LIMITED, 2022)
Build intelligent bots with a low-code design studio from SAP to automate repetitive manual processes and thus save precious labor hours and improve the business process efficiency Key Features Perform quick integration with an older system where building a standard integration might be too expensive Avoid erroneous data caused by inadvertent errors introduced by human actors due to lack of checks Increase productivity by working on high-value-added activities Book Description SAP Intelligent Robotic Process Automation (RPA) enables businesses to automate repetitive work and integrate automation capabilities across SAP and non-SAP systems. This book provides end-to-end coverage of business process automation using SAP Intelligent RPA and shows how to build multiple SAP Intelligent RPA projects from start to finish. Some of these projects may build upon the work done in previous chapters to showcase the Agile development process in SAP Intelligent RPA. As you progress, you'll cover the SAP Intelligent RPA factory, Desktop Studio, Cloud Studio, and the Bot store. You'll also learn about the building blocks of the SAP Intelligent RPA solution and creating bots from initial application declaration to workflow design and deployment, along with making bots run in attended and unattended modes. You'll also learn about SAP Process Automation, the new SAP service that is going to replace the SAP Intelligent RPA service soon. Finally, we will discuss the migration path for your SAP Intelligent RPA projects to SAP Process Automation and showcase that the RPA development remains similar in both services. By the end of this RPA book, you'll be able to create and manage complex bots that are capable of interacting with SAP and non-SAP systems. What you will learn Understand RPA and the broad context that RPA operates in Explore the low-code, no-code, and pro-code capabilities offered by SAP Intelligent RPA 2.0 Focus on bot development, testing, deployment, and configuration using SAP Intelligent RPA Get to grips with SAP Intelligent RPA 2.0 components and explore the product development roadmap Debug your project to identify the probable reasons for errors and remove existing and potential bugs Understand security within SAP Intelligent RPA, authorization, roles, and authentication Who this book is for This book is for developers and business users who are interested in learning SAP Intelligent RPA for automation of non-value-added, monotonous, and error-prone work. A basic understanding of JavaScript programming is required to engage in pro-code development for addressing complex challenges.